Care, co-survival, and decency: expanding the understanding of outdoor life and smaller alcohol and drug scenes in Denmark and Norway - Bach, Jonas Strandholdt; Grønnestad, Trond Erik; Selbekk, Anne Schanche; Bye, Vilde Holan; Skjong, Amanda (Frontiers in Psychiatry, 2024)
Introduction Public spaces where alcohol and other drugs are openly used and marginal citizens gather, exist in many Nordic cities. The biggest open drug scenes in the Nordic countries are in cities like Oslo and Copenhagen; however, there are smaller scenes in other cities and suburbs, centered around shed-like structures, offering some form of shelter and a designated space for marginalized people involved in heavy drug and alcohol use who hang out in public space. In this paper, we investigate, in a comparative perspective, the characteristics and functions of smaller open alcohol and drug scenes, and how their existence is negotiated in the local community and among the citizens using them. Methods and material This article is a comparative case-study based on data from fieldwork (participating observation and interviews) carried out in two specific, yet somewhat similar, locations in Denmark and Norway between 2017 – 2022. A cross-case analysis was performed to identify commonalities and differences. Results Smaller open alcohol and drug scenes are non-regulated spaces of ambivalence and ongoing negotiation in local communities. Based on the data across locations, they represent possibilities for informal care and community for citizens in marginalized situations. The scenes are further, across location, characterized by a mutual agreement of performing decency, e.g., not allowing minor drug sale/use. Discussion To enable public spaces as smaller alcohol and drug scenes can play a role in reducing harm for marginalized citizens. Communication and dialogue between citizens using an open drug scene and the wider community may help reduce stigma.